DESIGN OPTIMIZATION OF METRO KAPSUL BOGIE FRAME USING TOPOLOGY OPTIMIZATION - Nizar Aji Muhammadi, Ihdi
Metro Kapsul is a mode of public transportation that is being developed by PT Teknik Rekayasa Kereta Kapsul (TREKKA), PT Bandung Mechatronic Center (BAMEC) and Bandung Institute of Technology over the past few years. In terms of design, the Metro Capsule as one type of vehicle is expected to have a design that has a strong structure but has a light mass. This research will try to use topology optimization to optimize the design of the Metro Capsule bogie frame. The optimization is done by modifying the bogie frame design to reduce its mass, while still considering the strength requirements and the manufacturability aspects of the design. Topology optimization has been successfully applied to the Metro Capsule bogie frame using ANSYS software and density-based method. For the target mass fraction of 75-85% and 65-75%, the topology optimization resulted in a total mass reduction of 9% and 14%, respectively. Modification of the bogie frame design using the topology optimization results as a guide resulted in a total mass reduction of 11.3% to 242.60 kg. This design has many holes with complex shapes, so a second modification was carried out which resulted in a decrease in total mass by 11.7% to 241.42 kg. The maximum stresses in the final bogie frame design for exceptional static load with transverse force in the direction of positive and negative x-axis scenarios are 463.29 MPa and 389.87 MPa, respectively. When compared to the initial design which has maximum stress values for the same scenarios of 375.66 MPa and 344.73 MPa, there is an increase of 23.3% and 13.1%. For the two loading scenarios, the factor of safety of the final bogie frame design is 1.51 and 1.80.